(untitled) (Medical Forum Monthly, 2024)
Objective: To Assess the Biogenesis of lysine by penicillium expansum using agricultural waste as energy sources. Study Design: Experimental study Place and Duration of Study: This study was conducted at the CMH Institute of Medical Sciences Bahawalpur from May 2018 to September 2018. Materials and Methods: The waste of Millet husk, sorghum husk and Banana stem were used throughout the study. Microorganism: Penicilliumexpansum was obtained from the Department of Botany, University of Glasgow, U.K. and was used in this study. The stock culture was maintained on agar slant, containing (G/L) dextrose 20: peptone 10: agar 20 and distilled water. The sterilized slants were inoculated with penicillium expansum and incubated at 27oC to obtained growth. Results: In present study paper chromatographic method was carried out for separation and identification of amino acids synthesized by penicillium expansum in the culture broth using different solvent systems, who indicates that the selection of filter paper, solvent mixture and other conditions for paper chromatography are very important, because these determine Rf values and degree of separation. Conclusion: This study concludes that biogenesis of lysine by penicillium expansum using agricultural waste as energy sources